Pengaruh Hydroplaning Terhadap Kinerja Performa Boeing 737 - Inseren Femaya Rumakiek; Dinda Miranda Listiantika; Verel Joustika Abdul Rahman; Hadi Prayitno; Nazima Nazima (Indonesia Civil Pilot Academy Banyuwagi, 2025)
Hydroplaning is one of the causes of aircraft accidents during takeoff or landing. This study aims to examine the phenomenon of hydroplaning on the performance of the Boeing 737 aircraft, especially during takeoff and landing. Hydroplaning occurs when the air layer on the runway reduces friction between the aircraft wheels and the runway surface, which can disrupt stability and increase the aircraft's stopping distance. The research approach in this study uses a qualitative approach and the analysis used is a literature study from indexed scientific journals, textbooks, research reports, and other reliable sources. The results of this study, this study states that hydroplaning has a high effect on the performance of the Boeing 737 aircraft, especially when landing on a wet runway. Hydroplaning can reduce the effectiveness of aircraft braking and increase stopping distance substantially. Therefore, it is important to consider the air thickness factor and ensure speed control procedure to reduce the risk of hydroplaning. As well as the shape of the tire threads which can also reduce the height when landing or taking off